STUDY ON POSITIONING AND VALIDATION OF ARTIST IN THE CULTURAL DOMAIN OF NUEVO LEÓN, MEXICO - Oliva Abarca, Jesus (Universidad Autónoma de Tamaulipas, 2018)
In this paper, it will be examined the conditions of positioning and the strategies by which an individual is accredited as a cultural agent. This research focuses on the analysis of a specific cultural actor, the artist, and its incorporation and development in the artistic field of the Mexican state of Nuevo León. The research design chosen was descriptive, while qualitative methodology was the most accurate approach for this subject. To obtain pertinent data from the involved actors, the semistructured interview was the research strategy chosen. The sample was constructed on the participation of eleven experts. The information obtained was analyzed by structuring the data collected in descriptive themes. From the results, it can be highlighted that, in order to gain a position inside the artistic field, an artist must be capable of fulfilling different roles, as creator, as a promoter, or as a professor. Also, his/her validation as a cultural agent will depend on his/her involvement in institutional contexts.